Society 5.0: Is It High-Order Thinking? - Supendi, Ahmad; Nurjanah, Nurjanah (International Conference on Elementary Education, 2020)
Nowadays, the evolution of technology develops very quickly so that there is a challenge to be faced by the society. This evolution is due to the era of Industry 4.0 which the development of Information and Communication Technology (ICT) developed rapidly in this era. In the era of Industry 4.0, people are easy to get information quickly, innovation in the field of industrial technology is growing rapidly, and the emergence of Artificial Intelligence (AI) so that it causes changes to people in different countries. In 2016, to anticipate these changes Japan presented an idea namely society 5.0 or better known as a â€œSuper Smart Societyâ€. In fact, society 5.0 is not easy, some must be prepared one of them is to prepare students in education. In the educational world, to realize society 5.0, students must have three high abilities namely: problem-solving skills, critical thinking, and creativity. These three abilities are obtained through high-order thinking. This article reviewed some researches which focus on society 5.0 and the high-order thinking skills. This article aims to describe a high-order thinking ability to prepare students toward society 5.0